Comparative study of different Doppler spectrum estimator implementations - Madeira, M. M. (2015)
This paper presents a comparative performance study of some parallel processing architectures aiming at real-time implementation of a blood flow spectral estimator. Three homogeneous and an heterogeneous architecture incorporating transputers, digital signal processors (DSP's) and a vector processor were considered. The performance of these architectures was evaluated and compared in terms of execution times and gradient measurements. Communication times among processing elements were also considered. Analysis of the results revealed that both the DSP's homogeneous architecture and the heterogeneous architecture met real-time requirements; the latter presenting better execution times with less communications time load.